Replik om forførelse: Karen Blixens Ehrengard - Kondrup, Johnny (Danske Studier, 2024)
Karen Blixen’s story Ehrengard (published posthumously in 1963 and in an abridged English version in 1962) represents a pendant to Søren Kierkegaard’s »The Diary of a Seducer« from Either/Or (1843). Ehrengard is a response on behalf of Cordelia, the object of the seducer’s attentions. In Blixen it is the famous painter and privy councillor Johann Wolfgang Cazotte (with character traits similar to Goethe, as both Blixen and Kierkegaard imagined him), who wishes to seduce the Amazon-like simplicity and chastity that is Ehrengard. True to his reflected, intellectual relation to seduction, he does not wish to take Ehrengard’s virginity, but to make her blush brightly, when she becomes conscious of her erotic passion and at the same times realizes that it collides with a set of moral norms. He fails several times in his undertaking, and ultimately he is the one who blushes because Ehrengard points him out as the father of a child that she claims is hers and thus destroys his position as an aesthetic spectator. Blixen’s story claims that women can develop reflection without experiencing a split in their essential character, and thus undermines the Christian-patriarchal view which Kierkegaaard’s seducer shares with his author.